2020
DOI: 10.3390/d12020052
|View full text |Cite
|
Sign up to set email alerts
|

First Study on Marine Heterobranchia (Gastropoda, Mollusca) in Bangka Archipelago, North Sulawesi, Indonesia

Abstract: As ephemeral, benthic, secondary consumers usually associated with sessile coral reef organisms, marine heterobranchs are good indicators of the health of marine tropical habitats. Thus, marine Heterobranchia have recently become a major target for monitoring programs. For this work, an extensive survey was made in Bangka Archipelago, the first of its kind in this area. Bangka Archipelago is composed of small islands and the adjacent coastline of North Sulawesi. The substrate is dominated by biogenic reefs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 33 publications
0
22
0
1
Order By: Relevance
“…The taxonomic status of Thuridilla gracilis is at present unclear. Recent works ( Yonow and Jensen 2018 ; Papu et al 2020 ) have highlighted the significant variability of specimens ascribed to the species and questioned the synonymisation of multiple white-striped species of Thuridilla ( Gosliner 1995 ; Rudman 2000b ) under the single species T. gracilis . Indications suggest that the breadth of specimens currently considered as T. gracilis encompass a complex of species ( Händeler and Wägele 2007 ; Yonow and Jensen 2018 ; Papu et al 2020 ) that requires a comprehensive analysis utilising both morphological and molecular means.…”
Section: Resultsmentioning
confidence: 99%
“…The taxonomic status of Thuridilla gracilis is at present unclear. Recent works ( Yonow and Jensen 2018 ; Papu et al 2020 ) have highlighted the significant variability of specimens ascribed to the species and questioned the synonymisation of multiple white-striped species of Thuridilla ( Gosliner 1995 ; Rudman 2000b ) under the single species T. gracilis . Indications suggest that the breadth of specimens currently considered as T. gracilis encompass a complex of species ( Händeler and Wägele 2007 ; Yonow and Jensen 2018 ; Papu et al 2020 ) that requires a comprehensive analysis utilising both morphological and molecular means.…”
Section: Resultsmentioning
confidence: 99%
“…It has been concluded that a rise in sea water temperature along a latitudinal gradient from the poles to the equator considerably increases biodiversity (e.g., Bickford et al, 2007). This is generally true for nudibranchs as there are many times the number of species in tropical waters compared to the number of species found in cold polar and temperate waters (e.g., Marshall & Willan, 1999;Martynov & Korshunova, 2012;Papu et al, 2020). However, for some groups of invertebrates biodiversity is higher in northern seas, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…According to our results, the hitherto unidentified specimen from Indonesia mentioned in Papu et al as Peronia sp. a 20 and in Maniei et al as P. sp.7 3 was placed in the clade 4, together with P. verruculata specimens from China and Australia. Therefore, we preliminarily assign this specimen from Indonesia to the species P. verruculata.…”
Section: Species Delimitation and Haplotype Networking Of Peronia Spementioning
confidence: 81%